Pengaruh Diskon, Digital Marketing dan Kualitas Layanan terhadap Keputusan Mendaftar Sebagai Mahasiswa Baru di STIE Surakarta - Putri Dini Octavia Ardiansyah; Gilang Habib Azky Pratama H.P (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This study investigates the influence of discount programs, digital marketing strategies, and service quality on prospective students’ decisions to enroll at STIE Surakarta. The increasingly competitive landscape of private higher education in Indonesia requires institutions to formulate effective marketing strategies that can address the expectations and behavioral tendencies of Generation Z. A quantitative approach was employed using survey data from 36 new students selected through purposive sampling based on their participation in discount-based admission programs. The research instruments were validated through correlation tests and demonstrated reliable internal consistency. Data were analyzed using multiple linear regression to identify both partial and simultaneous effects among the variables. The findings reveal that discount offers are the only variable that significantly affects enrollment decisions, indicating that financial incentives remain a dominant consideration for prospective students evaluating private tertiary education options. Meanwhile, digital marketing and service quality, although yielding positive regression coefficients, do not show significant partial effects. However, the three variables collectively have a significant simultaneous effect, suggesting that enrollment decisions are shaped by a combination of economic, promotional, and perceptual factors. The model explains 45.7% of the variance in enrollment decisions. These results highlight the need for higher education institutions to balance financial incentives with consistent digital marketing execution and improved service delivery. The study contributes to the expanding literature on student decision-making behavior and offers practical insights for strengthening competitive marketing strategies in private higher education.